2014
DOI: 10.1155/2014/960628
|View full text |Cite
|
Sign up to set email alerts
|

Partial Splenic Embolization with Transarterial Chemoembolization in Patients with Hepatocellular Carcinoma Accompanied by Thrombocytopenia

Abstract: Background. Thrombocytopenia often makes the introduction of systemic treatment difficult in patients with cirrhosis and hepatocellular carcinoma (HCC). We retrospectively evaluated the long-term effects of partial splenic embolization (PSE) with transarterial chemoembolization (TACE) in patients with HCC patients accompanied by thrombocytopenia. Patients and Methods. Twenty-one patients with HCC complicated by severe thrombocytopenia (platelet count, <5.0 × 104/mm3) were treated with PSE and TACE. Both the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…Several studies have reported the positive results on the efficacy of PSE for HCC patients with thrombocytopenia caused by liver cirrhosis and supported its use in the treatment of hypersplenism, which is consistent with our results 15232430. One prospective study from China, including 50 HCC patients with hypersplenism caused by cirrhosis, showed that platelet and leukocyte counts after combined one-step TACE/PSE treatment were significantly higher compared with baseline during the three-month follow-up period ( P < 0.001), whereas those after TACE alone were significantly lower compared with baseline ( P < 0.001) 15.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have reported the positive results on the efficacy of PSE for HCC patients with thrombocytopenia caused by liver cirrhosis and supported its use in the treatment of hypersplenism, which is consistent with our results 15232430. One prospective study from China, including 50 HCC patients with hypersplenism caused by cirrhosis, showed that platelet and leukocyte counts after combined one-step TACE/PSE treatment were significantly higher compared with baseline during the three-month follow-up period ( P < 0.001), whereas those after TACE alone were significantly lower compared with baseline ( P < 0.001) 15.…”
Section: Discussionsupporting
confidence: 92%
“…It may enable HCC patients with severe thrombocytopenia related to splenomegaly to undergo TACE procedures. Although several studies have reported the positive clinical results of combination therapy with PSE and TACE for HCC patients with severe thrombocytopenia, to the best of our knowledge, the long-term clinical results of more than 1 year of PSE treatment combined with TACE in HCC patients with severe thrombocytopenia have not been reported 152324. Therefore, the current study aimed to evaluate the long-term efficacy and safety of PSE combined with TACE in HCC patients with severe thrombocytopenia.…”
Section: Introductionmentioning
confidence: 96%
“…TACE is a minimally invasive operation; thus, there is no strict requirement in terms of a preprocedural PLT count. For HCC patients with a low PLT count, TACE is feasible if PLT transfusion is performed prior to the procedure (13,23). A previous study investigated partial splenic embolization in cirrhosis patients with reduced PLT counts, and reported no complications such as puncture site bleeding or skin/mucosal bleeding, whereas the PLT/WBC counts increased significantly following treatment (23).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigated partial splenic embolization in cirrhosis patients with reduced PLT counts, and reported no complications such as puncture site bleeding or skin/mucosal bleeding, whereas the PLT/WBC counts increased significantly following treatment (23). Ooka et al (13) performed TACE (n=32) and partial splenic embolization (PSE; n=32) simultaneously in 21 HCC patients with reduced PLT counts (24-49x10 9 /l). That study reported that, following TACE, the PLT count increased to >50x10 9 /l in 17 of the 21 patients, of whom 13 received systemic chemotherapy, and 2 of the 21 patients developed hematomas (6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation